PENGARUH STRATEGI COPING TERHADAP TINGKAT STRES PADA CAREGIVER INFORMAL YANG MERAWAT PENDERITA SKIZOFRENIA DI POLI RAWAT JALAN RUMAH SAKIT JIWA DR. SOEHARTO HEERDJAN JAKARTA BARAT - Citra Ayu Aprilia; Ria Maria Theresa; Rahmalia Dewi Fitriani (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2020)
Limited psychiatric healthcare and being chronic, schizophrenia makes schizophrenia patient’s family hold important role as informal caregivers. Objective of this research was to know demography characteristic distribution and impact of coping strategy against schizophrenia informal caregiver’s stress level at Dr. Soeharto Heerdjan psychiatric hospital, out-patient unit. Coping stress vary depends on individual characteristics. This research was set to observational analytic with cross sectional design. Subjects of research were 32 caregivers, adapting research instrument CSI-SF 32 items and PSS-14 items. The result of research, majority of the caregivers is a woman and middle adulthood age. Most of caregivers goes to work and tend more than 4 years with nursing time more than 6 hours /day. There was impact of coping strategy against stress level of schizophrenia informal caregivers (p = 0,006). Most used coping strategy was adaptive coping with medium stress level. Long term could increase caregivers burden, so that it can trigger stress and could lower caregivers mental health status and could affect the treatment quality for schizophrenia patient. Writer recommended psychiatric healthcare to put psychological awareness and psycho-education intervention of stress management for caregivers.